Mitigation Of Genotoxic Effects Of Cisplatin Through Some Dietary Antioxidants In Human Lymphocyte Chromosomes In Vitro - G.G.H.A. SHADAB; NUZHAT PARVEEN (International Journal of Pharma and Bio Sciences, 2011)
Curcumin has been used in traditional Indian medicine for many centuries for its anti-inflammatory and anticarcinogenic properties and Garlic is a popular spice added to several edible preparations and is a remedy for a variety of ailments. The protective effects of Curcumin and Garlic on cisplatin induced chromosomal aberrations have been determined in the human peripheral lymphocyte chromosomal aberration test in vitro. The results of treatments with Curcumin and Garlic indicated that they statistically significantly decrease the number of chromosomal aberrations and number of metaphases with aberrations induced with cisplatin, but they cannot completely protect cells from damage. The test concentrations of Curcumin (50 μg/ml) and Garlic (100 μg/ml) showed limited antimutagenic effect on cisplatin (1.0 μg/ml and 2.0 μg/ml) at 0, 24 and 48 hour of duration in reverse order. Curcumin and Garlic showed the most efficient anticlastogenic effect during simultaneous treatment with cisplatin. The result further strengthened the findings about the protective and antigenotoxic properties of these two natural dietary products.